2011
DOI: 10.1038/sc.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of heart rate at lactate minimum and maximal lactate steady state in wheelchair-racing athletes

Abstract: Study design: Prospective, experimental study. Objective: To investigate whether the heart rate (HR) at lactate minimum (LMHR)determined by means of a HR-guided lactate minimum test (LMT) corresponds to the HR at maximal lactate steady state (MLSS) in wheelchair-racing athletes. Setting: Institute of Sports Medicine. Methods: Eight well-trained wheelchair-racing athletes (mean age: 33±12 years; height: 169±12 cm; body mass: 59±11 kg; . VO 2peak : 2.76 ± 0.73 l min À1 ) completed a HR-guided LMT on a treadmill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…2011), horses (Gondim et al 2007;Miranda et al 2014) and as discussed in rats (de Araujo et al 2007;de Araujo et al 2012;Voltarelli et al 2002). Nevertheless, another studies also found that LM intensity underestimate the MLSS intensity (Carter et al 1999 ; Ribeiro et al 2009 Specifics phases of the LM could modifying the relationship between production and clearance of lactate, promoting a left displacement of the lactate curve and underestimating the LM intensity (Heck et al 1991;Carter et al 1999 ; Ribeiro et al 2009;Labruyere and Perret 2012;Perret et al 2012). Recently, Zagatto et al (2014) verified differences between intensity of LM determined after different ways of hyperlactatemia induction in cycling, attesting that blood acid-base balance during resting pause can alters the response of incremental phase.…”
Section: Discussionmentioning
confidence: 98%
“…2011), horses (Gondim et al 2007;Miranda et al 2014) and as discussed in rats (de Araujo et al 2007;de Araujo et al 2012;Voltarelli et al 2002). Nevertheless, another studies also found that LM intensity underestimate the MLSS intensity (Carter et al 1999 ; Ribeiro et al 2009 Specifics phases of the LM could modifying the relationship between production and clearance of lactate, promoting a left displacement of the lactate curve and underestimating the LM intensity (Heck et al 1991;Carter et al 1999 ; Ribeiro et al 2009;Labruyere and Perret 2012;Perret et al 2012). Recently, Zagatto et al (2014) verified differences between intensity of LM determined after different ways of hyperlactatemia induction in cycling, attesting that blood acid-base balance during resting pause can alters the response of incremental phase.…”
Section: Discussionmentioning
confidence: 98%
“…This is relevant because studies that used 0.5 mmol.l −1 (Sotero et al, 2009) or 0.7 mmol.l −1 (MacIntosh et al, 2002) did not observe differences between LMI and iMLSS. On the other hand, when the 1.0 mmol.l −1 was considered (Jones and Doust, 1998; Carter et al, 1999a; Knoepfli-Lenzin and Boutellier, 2011; Perret et al, 2012) the iMLSS was significant higher than the LMI (Table 3). …”
Section: Does the Lmi Indeed Estimate The Imlss?mentioning
confidence: 95%
“…Over the years, the LMT has gained popularity around the world, and its application has been seen in several contexts including studies with diabetes (de Oliveira et al, 2007; Oliveira et al, 2010), thrombocytosis (Beck et al, 2014b) and wheelchair-racing athletes (Perret et al, 2012). Despite the fact that important concerns were arisen so far, some questions remain requiring discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Target HR for the fi rst stage was calculated from HR at rest plus 60 % of HR reserve (HRR), which was determined by subtraction of HR at rest from HRmax. For the following stages, the increments of HR corresponded to 8 % of HRR or a maximal increase of 8 bpm in accordance with the protocol of Perret et al [ 15 ] . Ergometer resistance was manually adjusted to reach the predicted HR within 3 min and to keep the HR constant ( ± 2bpm) for the last 2 min of the stage.…”
Section: Test Protocol Maximal Testmentioning
confidence: 99%
“…In contrast to workload-guided protocols, the HR-based approach has a further advantage: it allows using the same kind of LMT protocol independent of the sports discipline or the fi tness level of the subject. Although this HR-based version of the LMT correlates with MLSS [ 15 ] , is highly reproducible, standardized and user-friendly [ 21 ] , it remains unclear whether the subject really has to reach extensive lactic acidosis in the fi rst part of the LMT to receive reliable and meaningful results. This question is interesting for several reasons.…”
mentioning
confidence: 99%